LGBTQI+ professional accountants and the consequences of stigmatization: An identity work perspective - Ghio, Alessandro; Malsch, Bertrand; McGuigan, Nicholas (Contemporary Accounting Research, 2025)
Abstract Using a qualitative research design and drawing on an identity work perspective, we explore how LGBTQI+ professional accountants relate their self‐identity to their professional occupation and manage their stigmatized identity at work. Sharing original empirical data from focus groups and semi‐structured interviews with LGBTQI+ professional accountants, we show how they engage in inward‐facing identity work by resisting stigmatizing pressures by conceiving of a self that is both outside the norm (“deviant”) and adapted to it (i.e., a deviant‐adapted self). However, we also find that stigmatized identities can be embraced by participants as legitimate sources of distinct professional dispositions and a more powerful work ethic. This finding offers a less confrontational view of how marginalized identities and sexuality intersect with the accounting profession. In outward‐facing processes of identity work, we show considerable variations in how and when participants communicate about their stigmatized identity. Finally, we highlight the collective dynamic of stigma management as a fundamental condition of possibility for targets to overcome the limits of atomized individual action. However, this collective dynamic entails the risk of all targets being absorbed into a collective representation and social‐identity that either makes them invisible, or directly opposes certain aspects of their self‐identity. In this respect, we show how some of our participants actively contribute to the creation of a collective social‐identity to combat stigmatization within firms, which in turn generates symbolic power differentials and symbolic violence within LGBTQI+ professional accountants.